Innovative and transdisciplinary educational approach through the EDICULA toolkit - Roumeliotis, Stergios; Lampropoulos, Kyriakos; Lampropoulou, Antonia; Doulamis, Anastasios; Rallis, Ioannis; Georgopoulos, Andreas; Moropoulou, Antonia (Technical Annals, 2023)
The EDICULA educational toolkit regards an open source educational platform that addresses key issues in the rehabilitation, protection and sustainability of Cultural Heritage (CH) assets, and disseminates valuable knowhow and experience both to the wide audience as well as to CH stakeholders, scientists and professionals. The fundamental characteristic of this platform is that it promotes a holistic approach for transdisciplinary documentation, based on the experience and know-how of the EDICULA partners and – in the future – of the users as they will begin to utilize it. Both EDICULA toolkit modules are described after the development of the main thematic areas, the development of the toolkit on a moodle platform, and the preparation and uploading of the educational material. The access to the EDICULA educational platform, the layout of the educational platform, the types of educational material uploaded, the issues related to the toolkit-to-user information presentation approach and educational aspects, the complexities encountered and how they were overcome are being analyzed. The issue of users and degree of commonality between EDICULA-4-all and EDICULA+ educational toolkits is described. Emphasis is given on the way the modules are differentiated from one another. The access level is the main issue, which eventually provides a “smooth” transition between the two modules, ad hoc per user, under the supervision of registered and approved administrators or advanced users with editing privileges. The joint utilization of both the EDICULA-4-all and EDICULA+ toolkits in the educational, advisory or research processes, is at the core of the EDICULA project’s scopes.